Role of Energy Medicine in enhancing hemoglobin levels – A case study - Selvam, Mohanamathiyal; Jayapal, Praveena; Veerasamy, Ashtalakshmi; Sankar, Geetanjali (Indian Journal of Integrative Medicine, 2025)
Background: Anemia, characterized by low hemoglobin levels, often leads to fatigue, weakness, and diminished quality of life. Conventional treatments typically involve iron supplementation and dietary adjustments, but some cases remain resistant to these approaches. This case study explores the potential benefits of Acupuncture and Energy Medicine as energy therapies in managing anemia. Methods: A 43-year-old female with severe anemia (hemoglobin 6.5 g/dL) participated in a three-month treatment plan that combined acupuncture and energy therapy. Acupuncture targets specific points to enhance Qi flow, stimulate blood production, and restore energy balance. The energy therapy plan focused on blood-nourishing foods aimed at supporting hematopoiesis. Results: After three months of treatment, the patient’s hemoglobin levels increased by 4.9 g/dL, reaching 11.4 g/dL. Clinical symptoms, including fatigue, dizziness, and weakness, showed marked improvement. Additionally, the patient reported better sleep, enhanced mood, and an increase in appetite, all of which contributed to an improved overall sense of well-being. Conclusion: The results suggest that Acupuncture and Energy Medicine can serve as effective energy therapies in managing anemia, particularly for cases that do not respond well to conventional treatments. This case study provides preliminary evidence of their potential to improve hemoglobin levels and alleviate anemia-related symptoms. However, further research is necessary to validate these findings and explore the broader application of acupuncture and energy medicine in anemia management.